Investigation of sludge dewatering using Moringa oleifera as phytocoagulant - Abdulazeez, Qabas Marwan (Kulliyyah of Engineering, International Islamic University Malaysia, 2016)
Wastewater treatment plants produce large quantities of wastes every day. The most important waste generating from treatment processes is sludge, which consists of 98-99% water, solids, organic and inorganic constituents. The main process for sludge treatment is sludge dewatering that decreases the water content and increases solids concentration. Dewatering process can be done physically or chemically, and both techniques have negative effects. This study sought to investigate the use of Moringa oleifera (MO) seeds in sludge dewatering as natural coagulant in order to minimize the hazardous impacts on health and environment for chemical coagulants, and to eliminate the high cost and energy consumption of mechanical dewatering techniques. The first step in this study is the selection of the most effective extraction process of bioactive constituents from MO seeds. Seven forms of MO seeds were prepared and tested, which are crude MO seeds, defatted MO seeds, MO water extraction, and salts extraction by NaCl, NaNO3, KCl, and KNO3. Specific resistance to filtration (SRF) and supernatant turbidity were used to measure the dewatering efficiency of the different MO forms on synthetic sludge samples (kaolin suspension at 5% w/v). The first optimization was used to optimize the dewatering process conditions, which were the dosage of MO seed extract, pH, mixing time, while the second optimization was used to select the optimum ratio of a mixed coagulant consists of MO seed extract and aluminium sulfate (alum). A real sludge sample that collected from Bunus Sewage Treatment Plant, Kuala Lumpur, was compared with the synthetic sludge in terms of SRF, SVI, flocs shapes, filtration speed, settled flocs volume, and effect of pH. Results showed that the most effective extraction method was the extraction by NaCl (1 M). The optimum process conditions obtained from the first optimization were MO dosage of 235.6 mg/L, pH of 6.5, and mixing time of 21.2 min at SRF value of 1.1x1011 m/kg. ANOVA analysis showed that the model was significant and R2 was 95.6%. The optimum mixture ratio obtained from the second optimization was at 50% of MO and 50% of alum at SRF value of 0.8x1011 m/kg. ANOVA analysis showed that the model was also significant and R2 was 96.26%. Comparative results showed that the optimum mixing speed was 140 rpm for 60 min for real sludge, and 40 rpm at 21.2 min for synthetic sludge. The optimum dosages of MO seed extract were 800 mg/L and 235.6 mg/L for real and synthetic sludge, respectively. Real sludge required settling time of 120 min, which is twice longer than the settling time for the synthetic sludge. The optimum ratio of the mixed coagulant for real sludge was 10% for MO and 90% for alum at SRF value of 1.3x1011 m/kg. The use of MO either alone or mixed with alum can significantly minimize or even eliminate the hazardous impacts of chemical conditioners and involve MO in sludge treatment as a sustainable coagulant resource.